Flow and heat transfer to modified second grade fluid over a non-linear stretching sheet - Masood Khan; Masood ur Rahman (AIP Advances, 2015)
The objective of the present work is to analyze the two-dimensional boundary layer flow and heat transfer of a modified second grade fluid over a non-linear stretching sheet of constant surface temperature. The modelled momentum and energy equations are deduced to a system of ordinary differential equations by employing suitable transformations in boundary layer region and integrated numerically by fourth and fifth order Runge-Kutta Fehlberg method. Additionally, the analytic solutions of the governing problem are presented for some special cases. The secured results make it clear that the power-law index reduces both the momentum and thermal boundary layers. While the incremented values of the generalized second grade parameter leads to an increase in the momentum boundary layer and a decrease in the thermal boundary layer. To see the validity of the present results we have made a comparison with the previously published results as a special case with an outstanding compatibility.